Influence of disk brake friction on the dynamic behaviour of a directly coupled spur gear transmission. Issue 2 (5th August 2014) - Khabou, M.T.; Ksentini, O.; Jarraya, A.; Abbes, M.S.; Chaari, F.; Haddar, M.
Abstract : Purpose: – The purpose of this paper is to study the influence of friction phenomenon generated by a disc brake on the dynamic behaviour of a one-stage spur gear. Design/methodology/approach: – A theoretical model is proposed and is based on both theories of Coulomb and Dahl in order to analyse the influence of disc brake friction phenomenon on the dynamic behaviour of one-stage spur gear transmission. Findings: – The influence of brake friction on the dynamic behaviour of the transmission is investigated using the proposed model and leads to observe higher vibration levels when the braking is occurring as well as the emergence of significant efforts at the gear teeth. Originality/value: – A new numerical model based on the implicit numerical integration technique of Newmark coupled with Newton-Raphson method is proposed to study the influence of friction phenomenon of a disc brake on the dynamic behaviour of one-stage spur gear.